PENGARUH PENERAPAN PENDEKATAN PROSES TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN DI SEKOLAH DASAR - Pratiwi, Ervina Rizki; Kaswari, Kaswari; Uliyanti, Endang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this research was to determine the effect of whether there is influence ability to read comprehension by applying process approach for grade V students of SDN 33 north Pontianak.  Research methods that used is experimental method with Quasi Experimental Design, with Nonequivalent Control Group Design. The sample of this research are class VA consist of 28 students (experimen) and class VB consist of 25 students (control). Data collection techniques used are measurement a test instrument. Based on the statistical calculations obtained from the average result post-test experiment class is 74,50 and post-test control class is 61,00, obtained  tcount amount 2,113 and ttabel amount 1,677, because tacount > ttabel,then Ha accepted. So, can be concluded  that there is influence application process approach  to abilty to read comprehension for grade V students of SDN 33 north Pontianak. Based on calculation effect size (ES) = 0,53, with are criteria medium ,that is 0,2 > 0,8. Thus, it can be said that process approach influence the good one to abilty to read comprehension for grade V students of SDN 33 North Pontianak.  Keywords: Process Approach, Ability to Read Comprehension